Natural justice in adjudication - Ling, Tek Lee (2006)
Statutory Adjudication has been widely adopted by many countries and Malaysian construction industry is actively advocating to the Malaysia Government to enact this legislation to improve the present poor payment practices in the Malaysian construction industry. However, Adjudication with its rough nature of its processes is said to deliver rough justice. Therefore, this research thesis seeks to determine the relevant of the principles of natural justice in Adjudication through the decided cases in various jurisdictions. The research revealed that the principles of natural justice clearly apply in Adjudication. An Adjudicator is required to conduct the Adjudication proceeding in a way that will not lead to any element of bias or even on the perception of bias. Each party will be afforded an opportunity to present his case and to adduce evidence in support of his case. Nevertheless, the main challenge here is for the Adjudicator to maintain his sense of even handedness while managing the Adjudication proceeding in the midst of a very demanding timeframe. Decisions from the decided cases in various jurisdictions clearly show that the courts are prepared to consider the circumstances under which the Adjudicators operate and will undoubtedly enforced the Adjudicators’ determination unless there is a clear breach on the principles of natural justice within the main issue that is of considerable importance to the outcome